Role of tangeritin against cognitive impairments in transgenic Drosophila model of Parkinson's disease. (13th July 2019) - Fatima, Ambreen; Rahul,; Siddique, Yasir Hasan
Graphical abstract: Highlights: Effect of tangeritin on cognitive impairments in Drosophila model of Parkinson's disease. The PD flies were exposed to 5, 10 and 20 μM of tangeritin. Tangeritin reduces the cognitive impairments in PD flies. Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease. As there is no permanent cure for the disease, the use of herbal compounds with antioxidant potential will be an effective approach for controlling the progression of disease. In this context the effect of tangeritin (a polymethoxy flavone concentrated in the peels of citrus fruits) was studied at final doses of 5, 10 and 20 μM on PD model flies. The doses were established in diet and the PD flies were allowed to feed on it for 24 days. The effect was studied on cognitive impairments. Immunostaining of brain sections for tyrosine hydroxylase was also performed. The docking studies were also carried out to give a plausible binding site of tangeritin on alpha synuclein molecule. The results of the study showed that tangeritin is effective in improving the cognitive impairments.